2006
DOI: 10.1007/s10488-006-0033-7
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Primary Care Patients’ Preferences for Depression Treatment

Abstract: Despite efficacious treatments for depression in youth, current data indicate low rates of care. To better understand reasons for these low rates of care, we examined treatment preferences for depression treatment. Adolescents (N=444) who screened positive for depression at a primary care visit completed measures of predisposing, enabling, and need characteristics thought to be related to help seeking. Results indicated a strong tendency for adolescents to prefer active treatment (72%) versus watchful waiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 39 publications
2
50
1
Order By: Relevance
“…Female adolescents did not differ, compared with their male counterparts, in terms of preferences for medication treatment over counselling. 16 Therefore, the type of service provider adolescents and young adults with depression and suicidality see for treatment may be a result of the providers' preferences rather than the preferences of the patients themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Female adolescents did not differ, compared with their male counterparts, in terms of preferences for medication treatment over counselling. 16 Therefore, the type of service provider adolescents and young adults with depression and suicidality see for treatment may be a result of the providers' preferences rather than the preferences of the patients themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Among a population of adolescent primary care patients, 50% preferred psychotherapy, 22% preferred antidepressants, and 28% preferred to ''wait it out.'' (Jaycox et al 2006) Female adolescents prefer psychotherapy over antidepressants more strongly than males (Jaycox et al 2006). Previous experience with depression treatment and depressive symptom severity predict general preference for any active treatment over waiting it out (Gum et al 2006;Cooper et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Jaycox and colleagues found that despite a preference for psychotherapy, adolescent primary care patients fear rejection by peers if they saw a mental health professional (Jaycox et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially concerning given difficulties referring to specialty mental health. 3,11,12 Consistent with youth and parent pre ferences for nonpharmacologic treatments such as psychotherapy, [13][14][15] we examined whether a viable alternative could be effectively delivered in primary care: brief cognitive behavioral therapy (CBT). Although primary care CBT has been tested with depressed adolescents in several previous trials, 13,16,17 none specifically examined the effects of CBT in patients unreceptive to pharmacotherapy.…”
mentioning
confidence: 99%